Genetic and environmental factors affecting the epizootiology and pathogenesis of trypanosomiasis in livestock at eight sites within the African Trypanotolerant Livestock Network - D'Ieteren, G.D.M.; Awuome, K.; Bokovi, K.; Chema, S.; Coulibaly, L.; Defly, A.; Dumont, P.; Feron, A.; Grundler, G.; Handlos, Michael; Itty, P.; Jeannin, P.; et al. (OAU/STRC, 1988)
Studies the influence of livestock species, breed, age and lactational status on the prevalence, species and intensity of trypanosome infection in livestock at eight sites of the African Trypanotolerant livestock network in west, Central, and East Africa. Estimates the effect of trypanosome infections on the blood packed cell volume (PCV) of cattle for four characters, average PCV during gestation, at parturition, pre-weaning and at weaning. Reports also the effects of trypanosome infections on livestock viability, reproductive performance and live weights.